Corneal Diseases in Children : Challenges and Controversies - Colby, Kathryn (Springer International Publishing : Imprint: Springer, 2017)
This book provides comprehensive coverage of the most important corneal diseases in children, including congenital corneal opacities, infectious keratitis, corneal ectasia, ocular surface disorders and allergic eye disease. Highlights include an extensive discussion of corneal surgery in children, in-depth coverage of the role of various anterior segment ocular imaging modalities in the diagnosis and management of corneal diseases in the pediatric population, and surgical videos to further assist the reader. Chapters dedicated to amblyopia management and contact lens use in children round out the volume. Corneal Diseases in Children stands out as one of the few books dedicated to this important topic.
Keywords: Medicine.; Ophthalmology.; Pediatrics.; elektronické knihy; electronic books